Age-appropriate adaptation of creativity tasks for infants aged 12-24 months - Teo, Ling Zheng (2024)
Creativity is an important skill that relates to innovation, problem-solving and artistic achievement. However, relatively little is known about the early development of creative potential in very young children, in part due to a paucity of tasks suitable for use during infancy. Current measures of creativity in early childhood include the Unusual Box Test, Torrance's Thinking Creatively in Action and Movement (TCAM) task and the Toca Kitchen Monsters task. These tasks are designed for children aged above 12, 36 and 18 months respectively, but very few measures of creativity can be used for infants aged below 2. Accordingly, here we report age-appropriate adaptations of TCAM and Toca Kitchen Monsters tasks for infants as young as 12 to 24 months. Considerations taken into account include (1) infants' cognitive capacities (i.e., attention span, language comprehension skills, motor skills, and approach to play), and (2) practicality of the stimuli, including suitability for use amid the COVID-19 pandemic. The modified creativity battery for infants includes three tasks: Music Play, Object Play and Exploratory Play tasks. The task protocols elaborated in this paper are intended to facilitate studies on the early development of creativity in infants aged between 12 and 24 months. Primary highlights include: •Age-appropriate adaptation of creativity tasks for use with infants aged between 12 and 24 months. •Consideration of infants' cognitive capacities and stimulus practicality. •Innovative use of movement as expression of infants' creative behaviour.